Gq-Gi-PLCβ in cells: More than the sum of its reconstituted parts. (March 2021) - Wilkie, Thomas M.; Hale, Michael A.; Reddy, Sarthak
Abstract: The recent paper by Pfeil et al., "Heterotrimeric G Protein Subunit Gαq Is a Master Switch for Gβγ-Mediated Calcium Mobilization by Gi-Coupled GPCRs", opens another path from biochemical in vitro reconstitution to understanding the complex regulation of calcium signaling inside the cell.